Evaluating of VDR Gene Variation and its Interaction with Immune Regulatory Molecules in Osteoporosis - A Hossein-nezhad; Gh Ahangari; B Larijani (Tehran University of Medical Sciences, 2009)
Background: To evaluate VDR gene variation and its interaction with immune regulatory molecules in osteoporosis. Methods: Totally 205 pre and postmenopausal women were recruited in the study. After an overnight fast, peripheral blood was taken and centrifuged to sprat serum for measurement of serum parathyroid hormone, 25 hydroxyvitamin D, osteocalcin and cross laps. The FokI polymorphism in exon 2 of the VDR gene was detected by PCR-RFLP. Expression of osteoprotegrin, vitamin D receptor (VDR) and β-actin genes were quantified by quantitative real-time reverse transcriptase. To design the experimental model we randomly selected five participants of each genotype groups. PBMC were cultured and induced with vitamin D. At several times, cells were harvested and total RNA was extracted .Then expression of target genes evaluated by real time PCR. Results: The frequencies of Ff, FF and ff genotypes were 34.2%, 56.5% and 9.2%. The mean of bone mineral density in FF genotype was higher than other genotypes. Also in this genotype, mean of serum inflammatory cytokines was lower than other genotypes. The expressions of the VDR and osteoprotegrin were up regulated by 1, 25(OH)2D3 in PBMC from participants with FF genotype. PBMC from healthy control comparison to osteoporotic patients had a clearly better response to vitamin D3 incubation. Conclusion: Inflammation may important role in osteoporosis whereas osteoporotic patients have elevated pro-inflammatory profile. This cytokine profile and gene expressions of VDR and Osteoprotegrin were different in VDR genotype groups.